2006
DOI: 10.1001/archinte.166.14.1476
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation With 0.3-mg Recombinant Human Thyrotropin Prior to Iodine 131 Therapy to Improve the Size Reduction of Benign Nontoxic Nodular Goiter

Abstract: Stimulation with recombinant human thyrotropin prior to (131)I therapy improves thyroid size reduction by 35%, with a 5-fold higher rate of hypothyroidism. These effects are, at least partially, mediated through mechanisms other than an increase in retained (131)I thyroid dose. Further recombinant human thyrotropin dose-finding studies are warranted before routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 26 publications
8
80
2
Order By: Relevance
“…Combined with 131 I therapy rhTSH increases the GVR in MNG patients by 35-56%. This effect has been documented in three randomized controlled trials (RCT) depicted in Table 2 (17)(18)(19). In small-to-medium sized goitres (median goitre volume 51 ml, range 20-99 ml), we demonstrated that 0.3 mg of rhTSH improved the mean GVR by 33% at 1 year follow-up (Fig.…”
Section: Effect On Gvrsupporting
confidence: 68%
See 2 more Smart Citations
“…Combined with 131 I therapy rhTSH increases the GVR in MNG patients by 35-56%. This effect has been documented in three randomized controlled trials (RCT) depicted in Table 2 (17)(18)(19). In small-to-medium sized goitres (median goitre volume 51 ml, range 20-99 ml), we demonstrated that 0.3 mg of rhTSH improved the mean GVR by 33% at 1 year follow-up (Fig.…”
Section: Effect On Gvrsupporting
confidence: 68%
“…One study did not address this issue at all (19), whereas the other two studies (17,18) relied on a visual analogue scale (VAS). Before rhTSH-augmented 131 I therapy is implemented this issue deserves further attention.…”
Section: Effect On Gvrmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, data from our previous randomized controlled trials (14,15) indicate that mechanisms beyond the increase in the retained thyroid dose may be partially responsible for the beneficial effect of rhTSH in combination with 131 I therapy. In those studies, we found a positive correlation between the relative goiter volume reduction and the retained thyroid dose in the conventional (without rhTSH) 131 I therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…In 3 randomized controlled trials (13)(14)(15), rhTSH has been documented to enhance the goiter volume reduction by 35%256% when standard 131 I activities are used. An alternative strategy is to reduce the administered 131 I activity with a factor corresponding to the rhTSH-induced increase in RAIU.…”
mentioning
confidence: 99%